Bacterial contamination of table eggs in Babylon, Iraq: Muna sabbar Al-Rubiae1 and Hayder Hamzah Al- Taee2 - Al-Rubiae, Muna sabbar (The Iraqi Journal of Veterinary Medicine, 2014)
To study the bacterial contamination of table eggs in Babylon city, a total of 214 eggs collected from different sources, including 100 from farms and 114 from supermarkets, all samples were cultured for the bacteria on Salmonella Shigella Agar(SS Agar) and nutrient agar. The results of the farms samples showed that there are no growth of bacteria in all samples under study whereas the results of supermarkets samples showed that about 21.05% of supermarkets eggs were contaminated with bacterial strains, and the results showed the presence of Stahylococcus aureus in 10.52% of the samples, Pseudomonas aeruginosa in 7.89%, a Proteus mirabilis in 3.50%, S. epidermidis in 0.87% and Bacillus subtilis in 0.87%. Also, the antibiotic sensitivity tests were tested for all isolates and the result showed that the sensitivity was 100% for ciprofloxacin, 85.18% for gentamicin, 85.18% for Amikacin, 59.25% for rifampin, 48.14% for cefotaxime, 44.44% for chloramphenicol, 28.5% for clarithromycin and 0 % for cephalexin. The results showed there was not Salmonella spp. strains in all eggs samples so that present work tried to check the presence of Salmonella spp in farm chickens in farms, 213 chicken stool samples were collected from four farms, the samples were cultured on SS Agar, the results showed presence of Salmonella spp. in 10.37% of stool samples and the antibiotic sensitivity tested, also,the result showed that the sensitivity was 63.6% for ciprofloxacin, 86.36% for gentamicin, 86.36% for amikacin, 36.36% for rifampin, 27.27% for cefotaxime, 4.54% for chloramphenicol and 0% for cephalexin. The results indicated that there were 90% of the isolate of Salmonella spp. isolate have Multi-drug resistance phenomenon.